Toolkit for conducting citizen science activities in environmental epidemiology - Kocman, David; Righi, Valeria; Errandonea, Lucia; Maccani, Giovanni; Creus, Javier; Froeling, Frederique; Hoek, Gerard; Andrusaityte, Sandra; Grazuleviciene, Regina; Ficorilli, Antonella; De Marchi, Bruna; Biggeri, Annibale; et al. (Frontiers in Environmental Science, 2023)
Scientists and practitioners implementing citizen science projects, in which the involvement of citizens is key, often need ideas and tools that help in reaching citizens, engaging them in the project and maximizing their contributions. In this paper, we describe the creation of an open toolkit, a web-based portal citizensciencetoolkit.eu1 designed in the framework of the CitieS-Health project for the development and promotion of citizen science (CS) projects. The main focus is on projects linking urban environmental exposures and health, but it has applicability to other settings. The toolkit comprises the steps and phases during the implementation of CS activities in environmental epidemiology. A total of 28 tools are currently included, of which most were co-designed and tested within CitiesS-Health, as well as some resulting from external projects. For each tool, in addition to the details of its purpose and the specific challenges it poses, downloadable support content is available. To help facilitate inspiration and the adoption of tools provided, an illustrative step-by-step demonstration and description of its use in a CS project in a real-life setting is included, focusing on recommendations derived from the user experience. The portal is designed as a live inventory of tools, enabling interested CS practitioners not only to replicate, but also to continuously update and enrich it is content. To this end, the long-term objective of the portal is to act as a hub of resources that would enable the active inclusion of citizens in all the phases of the participatory research projects.